Analisis Prosedur Audit Internal terhadap Siklus Pembelian Tidak Langsung pada PT Barata Indonesia (PERSERO) - Aulia, Iftitah; Yuliati, Anik (IAI Nasional Laa Roiba Bogor, 2025)
The more complex a business is, the more optimized the internal control system must be. Management can carry out internal audits to evaluate the quality and performance of the company's internal control system. The inspections carried out cover the entire cycle of business activities in the company, one of which is the internal audit of the purchasing cycle. The purpose of this research is to determine the internal audit procedures for the indirect purchasing cycle used by PT Barata Indonesia (Persero). The method used in this research is a qualitative descriptive approach which obtain descriptive data in the form of words and images. The research results show that PT Barata Indonesia (Persero) has implemented an internal control system in carrying out its business activities. The internal audit procedure carried out by the company is a form of evaluating the quality, performance and effectiveness of the internal control system for the indirect purchasing cycle.